2019
DOI: 10.1002/ehf2.12436
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing can support physical activity in elderly patients with diastolic heart failure: results from a pilot study

Abstract: Aims Patients suffering from heart failure with preserved ejection fraction (HFpEF) report similar symptoms and reduction in quality of life to those with reduced ejection fraction but remain largely untreated. We conducted a preliminary evaluation of the acceptance, feasibility, and efficacy of a motivational interviewing (MI) intervention to support elderly patients suffering from HFpEF in maintaining or starting physical activity. Methods and results At the conclusion of the exercise training in diastolic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, few studies on exercise interventions among NMD have focused on the sustainability of acquired results of exercise programmes [23]. Based on other studies of chronic health conditions such as obesity [24] and heart failure [25], motivational interviewing (MI) seems to be a promising basis for implementation of a coaching programme in interventions to increase physical activity within the NMD population [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies on exercise interventions among NMD have focused on the sustainability of acquired results of exercise programmes [23]. Based on other studies of chronic health conditions such as obesity [24] and heart failure [25], motivational interviewing (MI) seems to be a promising basis for implementation of a coaching programme in interventions to increase physical activity within the NMD population [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 On the basis of a set of techniques aimed at facilitating the development and maintenance of certain behaviors, MI is delivered in the form of semistructured patient-centered visits during which patients examine and resolve attitudes of possible ambivalence and resistance to change. 11,15,16 Relatively few study authors have evaluated the effectiveness of MI in patients with HF, measured in terms of physical exercise, [16][17][18] hospital readmissions, 19 self-care, 11,17,[20][21][22][23] and HRQoL. 20,24 Furthermore, those studies have reported mixed results, partially explained by design limitations such as small samples and short follow-ups (<6 months).…”
mentioning
confidence: 99%
“…Indeed, patients with high self-efficacy, expectancy and self-determination are those who are more likely to be involved in a physical activity program and to maintain physical activity ( Sweet et al, 2011 ). However, when dealing with unmotivated patients, the use of a motivational intervention would be appropriate to induce engagement in the physical activity program ( Schertz et al, 2019 ).…”
Section: Futures Perspectives Of Researchmentioning
confidence: 99%